Molecular diagnosis of the 5q deletion in malignant myeloid disorders. - Boultwood, J (1996)
The 5q-chromosome is found in a spectrum of malignant myeloid disorders (1). The 5q deletion is the most commonly reported deletion in the myelodysplastic syndromes (MDS) and is found in 10-l5% of patients (1). The 5q-chromosome occurs as a sole karyotypic abnormality in the distinct myelodysplastic syndrome the 5q-syndrome (2). The 5q-chromosome is also observed frequently in therapy related MDS and acute myeloid leukemia (AML) where it is typically reported together with other karyotypic abnormalities (3). The 5q deletton is interstitial and the breakpoints are variable. The breakpoints most frequently reported are 5q12-q14 (proximal) and 5q3l-q33 (distal) (4). The most commonly reported 5q deletion is the del (5)(q13q33) (5). There appears to be no difference in the pattern of 5q deletion breakpoints between MDS and AML (4, 5).